Biodigestive septic tanks: Case study focused on the Santana do Aurá-Belém / PA School (Research, Society and Development, 2020)
The lack of access to water and basic sanitation is a barrier to disease prevention, a concern that extends for many years due to disease transmission. Currently, it is visible that the vast majority of people live without access to basic sanitation in Brazil, this lack of treatment can have serious socioenvironmental consequences. Thus, it is necessary to seek accessible technologies to treat domestic effluents, mainly in rural communities, in order to minimize negative impacts. It is worth mentioning that the launch directly into the water or soil, results in significant impacts on aquatic life and the environment as a whole. Therefore, the research carried out in partnership with Embrapa Amazônia Oriental-Belém / PA seeks to highlight the importance of the development of rural technology such as biodigestive septic tanks, developed by Embrapa to treat rural domestic sewage. The study was carried out at the Santana do Aurá-Belem / PA Municipal School, with the purpose of bringing quality of life to students and employees and showing that low-cost technologies are efficient to improve the sewage system within a community in the rural area. With the development of the project it was possible to identify that the biodigester septic tank can treat the generated sewage and did not leave it exposed as previously. It is also worth mentioning that the neighborhood where the project was installed does not yet have the correct sanitary sewage treatment and that other actions may extend beyond the school walls